Factors Affecting Organizational Success: A Case Study of Foodpanda - Nurhafizah Kamilah; Daisy Mui Hung Kee; Muhamad Syafiq; Shaidatul Aina; Hui San Yap; Adnan Abbas Alqallaf; Majdi Anwar Quttainah (Journal of the Community Development in Asia (JCDA), 2020)
The purpose of this study is to examine the success factors of Foodpanda. Foodpanda is one of the leading online food delivery marketplaces and is spread out globally. Its main job is to enable users to place orders at nearby restaurants with the assistance of its website or via its mobile app. The study used questionnaires to collect data from Foodpanda’s employees in addition to the customers that used Foodpanda apps in Malaysia. The result shows that employee loyalty, job satisfaction, and customer satisfaction are the factors that drive the success of Foodpanda.